19. Yüzyılın Son Çeyreğinde Malatya'da Yaşanan Afetler, Sosyal, Ekonomik Krizler ve Yardım Faaliyetleri - Abdurrahim Fahimi AYDIN (Gazi Akademik Bakış)
Disasters such as earthquakes, fires, famine, locust invasions and cholera caused unfortunate disasters in Malatya in the last quarter of the 19th century. In addition to all these, the immigrant and Armenian question has deepened the issues. Each devastating event triggered another disaster. Although the issues were tried to be resolved with local measures at the beginning, these measures were not sufficient. Problems were tried to be solved with the joint aid of the state and the people. The Ottoman Empire has acquired a number of principles while settling the refugees. The main purpose of these principles is to provide food for immigrants. An order has been established in which they can provide their salaries and shelter within the framework of humanitarian aid. The black market became widespread with the increase in demand for foodstuffs during the war years, the decrease in production and the cessation of imports as a result of the closure of transportation routes. The state has made intensive efforts to provide the necessary nutrients and basic consumer goods for the feeding of the poor people, the Army and civil servants, and to prevent price increases. In order to combat speculation, basic consumption items have been pledged. Cords and lazaretto were opened to combat the cholera epidemic, and the rest of the food was met. Due to the magnitude of the damage and financial loss in the earthquake, it was decided to collect aid for the victims of Malatya in all Ottoman provinces in order to heal the wounds of the disaster victims. While the people of Malatya were going through difficult times, they showed a good example of the fusion of the state and the nation, and carried out contractual activities with the state in needed areas.